Implementasi Pancasila Dalam Kehidupan di Masa Pandemi Covid-19 - Jamilla Agustin Ummu Sholih; Dinie Anggraeni Dewi (Universitas PGRI Adi Buana Surabaya, 2021)
This research aims to describe an overview of how the values ​​of Pancasila are implemented in the current conditions, namely Covid-19. The research method uses a qualitative approach or a descriptive approach. Which theory or basis for discussion is obtained from the results of literature studies from various sources such as journals, books and articles. Then, the results showed that currently without the public realizing that the implementation of Pancasila values ​​at the time of this pandemic began to increase. The existence of this epidemic makes the community more tolerant and open to helping each other. This activity is one of the applications of Pancasila values. So, Pancasila is essentially a view of the life of the nation and as a basis for the state in living.